2016
DOI: 10.1038/srep36274
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of trihelix genes and their expression under biotic and abiotic stresses in Populus trichocarpa

Abstract: Trihelix genes play important roles in plant growth and development and responses to biotic and abiotic stresses. Here, we identified 56 full-length trihelix genes in Populus trichocarpa and classified them into five groups. Most genes within a given group had similar gene structures and conserved motifs. The trihelix genes were unequally distributed across 19 different linkage groups. Fifteen paralogous pairs were identified, 14 of which have undergone segmental duplication events. Promoter cis-element analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 65 publications
10
36
0
Order By: Relevance
“…In addition, each group shares similar intron and exon structures. These results of motif and gene structure analysis are similar to the study of the poplar trihelix family (Wang et al 2016). The previous study found that the domains outside the bHLH domain may have diverse molecular functions in Arabidopsis (Toledo-Ortiz et al 2003).…”
Section: Discussionsupporting
confidence: 83%
“…In addition, each group shares similar intron and exon structures. These results of motif and gene structure analysis are similar to the study of the poplar trihelix family (Wang et al 2016). The previous study found that the domains outside the bHLH domain may have diverse molecular functions in Arabidopsis (Toledo-Ortiz et al 2003).…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, OsTIFY1a, -1b, -2a, -2b, AtTIFY1, -2a, -2b not only have a TIFY domain but also a GATA zinc-finger and a CCT motif; the remaining members in Rice and Arabidopsis do not have the CCT motif. However, almost all the PtrZML proteins contain the CCT motif, suggesting that woody plants might have undergone many different changes during the evolutionary process [37].…”
Section: Discussionmentioning
confidence: 99%
“…The number of trihelix found in the various cotton species is in agreement with previous findings, in which the members of the trihelix family have been found to be relatively low compared to other plant TFs family, such as MYBs, despite that trihelix genes are believed to have evolved from the MYBs (Nagano ). To date, 30, 31, 52 and 80 trihelix gene members have been identified in Arabidopsis (Kaplan‐Levy et al ), Oryza sativa (Qin et al ), Brassica rapa (Wang et al ) and Populus trichocarpa (Wang et al ), respectively. The low numbers of the trihelix genes in plants show that they are the most recent genes to evolve, and this could be linked to the environmental changes the plants are currently being exposed to.…”
Section: Discussionmentioning
confidence: 99%